Effects of Alirocumab and Evolocumab on Cardiovascular Mortality and LDL-C: Stratified According to the Baseline LDL-C Levels - Hui Ma; Wenfang Ma; Yang Liu; Lixing Chen; Peng Ding (Reviews in Cardiovascular Medicine)
Background: A meta-analysis was conducted to determine whether the cardiovascular mortality and lipid-lowering effects of alirocumab and evolocumab are influenced by various baseline low-density lipoprotein cholesterol (LDL-C) levels. Methods: We searched for literature published before June 2023. Eligible randomized controlled trials (RCTs) included adults treated with alirocumab or evolocumab and reported LDL-C changes and cardiovascular deaths. The primary endpoints were cardiovascular mortality and percent changes in LDL-C from baseline. Results: Forty-one RCTs were included in the meta-analysis. Evolocumab did not significantly affect the outcome of cardiovascular mortality whether the baseline data were greater than 100 mg/dL or less than 100 mg/dL. However, the stratified result showed that alirocumab decreased the risk of cardiovascular mortality in patients with a baseline LDL-C level of ≥100 mg/dL (relative risk (RR) 0.45; 95% CI: 0.22 to 0.92; p = 0.03). In terms of lipid-lowering efficacy, alirocumab (mean difference (MD) –56.62%; 95% CI: –60.70% to –52.54%; p < 0.001) and evolocumab (MD –68.10%; 95% CI: –74.85% to –61.36%; p < 0.001) yielded the highest percentage reduction in LDL-C level when baseline levels were 70–100 mg/dL, while the smallest reduction in alirocumab (MD –37.26%; 95% CI: –44.06% to –30.46%; p < 0.001) and evolocumab (MD –37.55%; 95% CI: –40.47% to –34.63%; p < 0.001) occurred with baseline LDL-C levels of ≥160 mg/dL. Conclusions: Alirocumab and evolocumab presented a better lipid-lowering effect when the baseline LDL-C levels were <100 mg/dL. Alirocumab was associated with a significant reduction in cardiovascular mortality at baseline LDL-C levels of ≥100 mg/dL. This finding can have significant implications for the development of personalized drug therapy. The PROSPERO Registration: CRD42023446723, https://www.crd.york.ac.uk/PROSPERO/view/CRD42023446723.